Prevalence of Dental Caries Among Children Aged 6-12 Years in A Govt. Primary School in Siddhirganj (Journal of Dentistry and Allied Science, 2025)
Among chronic oral diseases, dental caries is the most common, especially in children. It is a progressive infectious process with a multifactorial etiology. The study is conduct to assess the prevalence of dental caries and associated factor among children aged 6-12 years in a govt. primary school. It was a descriptive type of cross-sectional study.The study was conducted in Siddhirganj government primary school, Narayanganj, Bangladesh. Duration of the study was 6 months from 1st January 2022 to 30th June 2022. Population of this study was all the children of class I to class V (8-12 years of age group). In this study we found those who had very good and good health condition were less suffered by caries incidence and those who had poor and very poor the health condition incidence of caries was high.Primary schools have a great potential for influencing health behavior of the children. Systematic training programs for teachers, give priority to community-oriented oral health care and strengthening of preventing programs through the joint efforts of dental auxiliary and the general public can help reduce the need for treatment. Conclusion: This study provides preliminary reference values for salivary LDH in healthy adults, which may support future diagnostic applications. Further research on larger, demographically diverse populations is warranted.Journal of Dentistry and Allied Science, Vol. 8 No 2: 54-66